Keterampilan Berpikir Kreatif Peserta Didik yang Diajar Melalui Model Pembelajaran Pjbl dan Model Konvensional Materi Pencemaran Lingkungan - Ashriah, Sitti; Muis, Abd.; Arsal, A. Faridah (Biology Teaching and Learning, 2020)
Abstract. This research aims to find out the difference of students’ creative thinking skill using the PjBL learning model and conventional learning model for environmental pollution material. This research is a quasi-experiment with pretest-posttest control group design. The population were all the students of class VII and the sample were 34 students of class VII A and VII C. Data collection techniques used an essay. Data analysis in this study was conducted by t-test. The results showed that (1) creative thinking skill of students taught using PjBL learning model of environmental pollution material are in the moderate category with an average value of 58.23; (2) creative thinking skill of students taught using conventional learning model of environmental pollution are in the low category with an average value of 46.70; (3) there is difference of students’ creative thinking skill using PjBL learning model and conventional learning model of environmental pollution materials where students taught through PjBL learning model have higher creative thinking skills than taught by conventional learning model.Keywords: creative thinking skill, project-based learning, coventional learning.